Capital in the twenty-first century - Piketty, Thomas; Goldhammer, Arthur (Cambridge, MA Havard University Press, 2013)
This book by Thomas Piketty analyses a unique collection of data from twenty countries, ranging as far back as the eighteenth century, to uncover key economic and social patterns. His findings will transform debate and set the agenda for the next generation of thought about wealth and inequality. Piketty shows that modern economic growth and the diffusion of knowledge have allowed us to avoid inequalities on the apocalyptic scale predicted by Karl Marx.
Includes bibliographical references (pages 579-655) and index.
lje 24/10/17
Loans
Keywords: Capital; Income distribution; Wealth; Labor economics